Kualitas Pemesinan Kayu Punak (Tetramerista glabra Miq.) Menurut Kedalaman Batang - Achmad Supriadi (Institut Pertanian Bogor, 2019)
This paper presents the results of the quality of wood machining according to the depth of the stem. Testing of machining properties refers to modified ASTM D-1666-64. The results showed that the quality of wood machineries of the outside of the steam was fair to good and the inside of the steam was good to excellent. The fuzzy grain was most found. The quality of wood inside the stem is generally better than the outer wood. The depth of the stem has a significant effect on the value of defect free turning. Punak wood can be recommended to be processed into a variety of wood working products such as moulding, wood carvings, pegs, fence, the other items of turnings, panels, door components, tables, and wallcoverings.